Practical guidelines for development of a university-wide faculty mentorship program using a multimodal mentoring network model - Matthew Gabriel Schwartz (To Improve the Academy)
Formal faculty mentorship programs are a practical and effective pathway to enable faculty success in teaching, scholarship, and service and to enhance faculty satisfaction. Although informal mentoring relationships benefit some faculty, formal faculty mentorship programs ensure equitable access to mentorship for female faculty and faculty from diverse, underrepresented backgrounds. Formal faculty mentorship programs can utilize a variety of structures, each with their benefits and drawbacks. This article recommends a multimodal mentoring network model to harness the benefits of traditional dyadic mentoring, multiple-mentor mentorship, peer and near-peer mentorship, and topic- and affinity-based group mentorship and to confer the flexibility, adaptability, and support needed to best cater to the career and psychosocial needs of a diverse faculty. In addition to identifying a suitable program structure, creating a successful university-wide faculty mentorship program requires consultation with faculty of all levels, collaboration with multiple campus departments and stakeholders, and highly visible support from senior administrators. Successful implementation and maintenance of a multimodal university-wide faculty mentorship program also requires appropriate resources and incentives to build and sustain a culture of faculty participation. This article provides practical, evidence-based recommendations for the successful design and implementation of a multimodal university-wide faculty mentorship program.Note: This article has been amended since its initial publication in order to properly credit foundational research developed by scholars of color. Please see the Correction Notice (https://doi.org/10.3998/tia.4970) for additional details.